Functional movement screen and Y balance tests in adolescent footballers with hip/groin symptoms. (September 2019) - Linek, Pawel; Booysen, Nadine; Sikora, Damian; Stokes, Maria
Abstract: Objectives: To assess the correlation between the functional movement screen (FMS) and Y balance test (Y-BT) performance, and the self-reported hip/groin problems, and to compare healthy with hip/groin pain participants. Design: a cross-sectional study. Setting: Sports hall in a football club. Participants: 43 elite adolescent football (soccer) players. Main outcome: The Copenhagen Hip and Groin Outcome Score (HAGOS), Anterior, posterolateral and posteromedial distance of Y-BT, FMS score. Measures: Y balance and FMS test kit, HAGOS questionnaire. Results: The posterolateral, posteromedial distance and composite reach score of the Y-BT were lower in participants with hip/groin problems (p < 0.05). FMS performance was similar in healthy and hip/groin groups. There was a weak correlation ( r  = 0.32, p = 0.03) between the HAGOS Activities of Daily Living subscale and FMSstabil . In the Y-BT the posterolateral reach was weakly correlated with Symptoms (r = 0.35–0.44, p < 0.02) and moderately correlated with Pain (r = 0.44, p < 0.01) subscales. Posteromedial direction reach with the right leg was weakly correlated with Symptoms (r = 0.32, p = 0.04) and Pain (r = 0.39, p = 0.01). The Y-BT composite score was moderately correlated with Symptoms and Pain (r = 0.42–0.44, p < 0.01). Conclusions: The Y-BT and the FMS subtests were weakly or moderately correlated with self-reported hip/groin problems. Thus, these tests should be investigated further in adolescent footballers because they may have potential to predict hip and groin problems. Highlights: Y balance test results were associated with hip and groin symptoms and pain. The trunk stability push-up and rotatory stability test of the FMS were associated with hip/groin symptoms. The FMS and Y balance test should be investigated further in studies of adolescent footballers with hip/groin problems.